Experimental study the effects of various compression ratios and spark timing on performance and emission of a lean-burn heavy-duty spark ignition engine fueled with methane gas and hydrogen blends. (15th February 2019) - Duan, Xiongbo; Li, Yangyang; Liu, Jingping; Guo, Genmiao; Fu, Jianqin; Zhang, Quanchang; Zhang, Shiheng; Liu, Weiqiang
Abstract: To investigate effects of various compression ratios (CRs) and spark timing on characteristics of performance and emissions, a high CR six-cylinder heavy-duty compression ignition diesel engine was modified into the port fuel injection hydrogen and liquefied methane gas lean-burn heavy-duty SI engine and tested by using 13.6 and 14.0 CRs. Combination of alternative fuels, high CRs and control strategies was implemented in this study. Results indicated that the equivalent fuel consumption (EFC) dramatically decreased with increase of the hydrogen energy share. Additionally, the EFC reduced as higher CR was adopted. The brake thermal efficiency (BTE) firstly increased and then declined with increase of the hydrogen energy share. Besides, the BTE increased with CR. The maximum additional 1.8% of BTE was obtained by employing higher CR (14.0) for a specific operating condition. Furthermore, the NOX emissions remarkably ascended while the HC emissions significantly declined with increase of the hydrogen energy share. The CO emission formation did not show a strong relationship with the hydrogen energy share and the CR. However, the CO2 emission gradually declined with increase of the percentage of hydrogen and CR. Highlights: A comparative investigation of various high CRs and spark timing on a lean-burn heavy-duty SI engine. Equivalent fuel consumption decreased with the increase of hydrogen energy share and CRs. The maximum additional 1.8% of BTE was obtained by employing higher CR (14.0).